Impact of Axis of GHRH and GHRH Receptor on Cell Viability and Apoptosis of the Placental Choriocarcinoma Cell Line - Liu, A.-X.; Zhang, D.; Zhu, Y.-M.; Gao, H.-J.; Jiang, J.-Y.; Hu, X.-L.; Lv, P.-P.; Leung, P.C.K.; Huang, H.-F. (Current Molecular Medicine, 2016)
Although GHRH and GHRH-R are recognized as key factors in placental development, little is known about the mechanism(s) of the regulation in trophoblastic cells during placental development. The objective of this study is to determine the potential relationship between the expression levels of GHRH-R and the placental and JEG-3 cell function. Furthermore, we aim to investigate the downstream pathways of GHRH/GHRH-R axis in the control of the JEG-3 cell viability and apoptosis. In this study, we detected the expression pattern of GHRH-R in human chorionic villous tissues and JEG-3 cell. Then, we evaluated the effects of GHRH/GHRH-R and the downstream pathways by using GHRH antagonist (JMR-132) on JEG-3 cell. Our present study found the expressions of GHRH-R in placental villous tissues and JEG-3 cell, and the expression levels of GHRH-R was significantly lower in villous tissues of early pregnancy loss when compared to normal controls. JMR-132 inhibited cellular viability and induced apoptosis in JEG-3 cell in a time and dosedependent manners through activation of caspase-3, p38, and p53, as well as inhibition of phosphorylation of Akt. Interestingly, ER stress markers such as GRP78, ubiquitinated proteins and phospho-eIF2α were significantly increased in JEG-3 cell after being treated with JMR-132. Conversely, pretreated with salubrinal (a selective inhibition of protein phosphatase 1-mediated eIF2α dephosphorylation), JEG-3 cells were rescued from JMR-132-mediated cell growth inhibition, and abolished JMR-132-induced cleaved caspase-3, CHOP, phospho-p53, and ubiquitinated proteins accumulation. Knockdown of endogenous GHRH-R significantly abolished the JMR-132-induced cleaved caspase-3 and activation of p38. In conclusion, our results, for the first time, demonstrated the expression levels of GHRH-R were closely related to the placental function. Inhibition of GHRH-R by using GHRH antagonist in JEG-3 cell may reduce cell viability and induce apoptosis through inactivation of Akt and ER stress via phosphorylation of eIF2α. These observations have enriched our understanding on the function of GHRH/GHRH-R axis and the downstream pathways in the control of the placental development. The Most Important Aspect of the Paper: Our present study for the first time provided evidences that GHRH and GHRH-R loops involve in JEG-3 cell viability and apoptosis through Akt and eIF2α pathways.
Keywords: viability